(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study was to examine the effects of computer media instruction on secondary school students’ retention in Basic Technology in Awgu Local Government Area of Enugu State. Two research questions were answered while three hypotheses were tested. The study adopted a factorial research design using intact classes. A 2x3 factorial model was employed in the study. A sample of 118 Junior Secondary School two (JS2) Basic Technology students from Awgu Education Zone of Enugu state was used in the study. The instrument for data collection was Basic Technology Retention Test (BTRT) and was validated by four experts. The reliability of the instrument was established using Kudder-Richardson formula 20 which yielded coefficient of internal consistency of 0.92. Teachers were trained as research assistants and they administered the treatment on the students using the designed lesson plans. The method of data collection was by administering the BTRT as pretest and posttest after two weeks of treatment. The data obtained were analyzed using mean gain and Analysis of Covariance (ANCOVA). The results revealed among others that the students taught basic technology using computer media instruction performed better and had an improved retention than those in the conventional lecture method. There was a significant difference between the retention of students in basic technology in the computer media instruction group and conventional method in favour of computer media instruction. Based on the findings, the study recommended among others that basic technology teachers should adopt computer media instruction to involve students in the learning process actively and make them take more responsibility for their own learning